It's all in the timing: The effect of a healthy food cue on food choices from a pictorial menu. (1st August 2019) - Tonkin, Michelle; Kemps, Eva; Prichard, Ivanka; Polivy, Janet; Herman, C. Peter; Tiggemann, Marika
Abstract: The contemporary food-rich environment has been consistently linked to unhealthy eating. Emerging research suggests that changing the presentation context of unhealthy foods by introducing a subtle nudge in the form of a healthy food cue may promote healthier dietary choices. This study investigated the effect of the timing of a healthy food cue (before or simultaneously with food options) on food choices. Participants ( n = 210) were presented with a pictorial café-style menu displaying a healthy food cue (basket of fruit and vegetables) either on the menu cover or inside the menu, or they received a control menu. Participants were asked to make one choice from each of three menu sections (meals, beverages, afters), and then completed a measure of dietary restraint. As predicted, participants chose a greater proportion of healthy food from the healthy-cue-before menu compared to both the healthy-cue-simultaneous and control menus. Furthermore, this effect was stronger for restrained eaters. The findings demonstrate that the timing of presentation of a healthy food cue is critical, and could be used to inform the design of menus in real-world environments, such as cafés and fast-food outlets, to promote healthier dietary choices.